Women’s Unequal Standing Within International Security and Human Rights - Lišková, Kristýna (2018)
This master’s thesis evaluates the generally unequal position of women under the security threats. This work emphasizes the security of individuals and the equality of gender. Feminist perspectives towards security are, therefore, applied within this piece, in order to characterize the gender-related suffering and demonstrate that gender is more than just belonging to some classes. The gender unfairness is demonstrated on the situation of the Iraqi women during the sanctions regime that the United Nations imposed on Iraq. It is assumed, that in the numerous instances, typical female characteristics caused, that the Iraqi women experienced additional suffering to the suffering that the society experienced as a whole. Typical women difficulties such as the inequality in working and educational opportunities, the difficulties related with poor access to food and drinking water, and plights resulting from the insufficient healthcare are addressed in this master’s thesis. Even though these troubles challenged Iraqi men as well, this work assumes that Iraqi women were experiencing additional harms, as the Iraqi society is characterized as masculine.